Please sir, I want some more: an exploration of repeat foodbank use - Garratt, Elisabeth (BMC Public Health, 2017)
BACKGROUND: The sharp rise in foodbank use in Britain over the past five years suggests a proliferation of food insecurity that could herald a public health crisis. However, trends in foodbank use rely on imperfect figures that do not distinguish between single and repeat visits. Consequently, the true prevalence of foodbank use in Britain is unknown. By identifying repeat visits, this study provides the first estimate of the proportion of people using foodbanks. METHODS: Using data on referrals to West Cheshire Foodbank in the UK, this study offers a case study of 7769 referrals to one foodbank between 2013 and 2015. Foodbank use was explored in descriptive statistics, then negative binomial regression models were used to identify the household characteristics associated with the number of foodbank visits. RESULTS: Between 0.9 and 1.3% of people in West Cheshire sought assistance from West Cheshire Foodbank between 2013 and 2015. If scaled up nationally, this would equate to an estimated 850,000 people across Britain. The number of total recipients increased by 29% between 2013 and 2015, while the number of unique recipients rose by 14%. Multivariate analysis revealed that a larger number of visits were recorded in 2015 and among working-age and one-person households, while households referred due to domestic abuse and unemployment made fewer visits. CONCLUSION: Food insecurity has emerged as a crucial challenge facing UK health professionals and policymakers. This study provides the first estimate of the proportion of individuals receiving emergency food in a single case study location, and demonstrates that foodbank use is becoming more prevalent, although headline figures overstate the scale of this growth. The potential nutrition and wider health consequences of reliance on emergency food – especially among those using foodbanks on multiple occasions – warns of an unfolding public health crisis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12889-017-4847-x) contains supplementary material, which is available to authorized users.